Answer:g=3x
Explanation:
I wrote this in the comments to but now it’s allowing its allowing me to answer so here: simplify the left side by distributing the values and it turns out to be x^2+3x-28 and the right side stays the same. We write this as x^2+3x-28=x^2+g-28. We then simply by the addition property of equality by adding 28 to both sides. We are left with x^2+3x=x^2+g. We then subtract x^2 from both sides ending up with g=3x.
Answer:
g=3
(x+7)(x-4)=x(x-4)+7(x-4)=x²-4x+7x-28=x²+3x-28
it should be gx ,then g=3
if ge then ge=3x
5.4m questions
7.0m answers